Defect-rich N-doped CeO2 supported by N-doped graphene as a metal-free plasmonic hydrogen evolution photocatalyst. Issue 16 (13th April 2021) - Van Dao, Dung; Jung, Hyun Dong; Nguyen, Thuy T. D.; Ki, Sang-Woo; Son, Hoki; Bae, Kang-Bin; Le, Thanh Duc; Cho, Yeong-Hoon; Yang, Jin-Kyu; Yu, Yeon-Tae; Back, Seoin; Lee, In-Hwan
Abstract : We reported a plasmonic photocatalyst consisting of N-CeO2 supported by N-graphene for light-driven HER, which offered a superior performance relative to N-CeO2 and CeO2 catalysts. This could be due to the plasmonic effects of N-CeO2 and excellent conductivity of N-graphene. Abstract : Heteroatom doping into metal oxides advantageously modulates optoelectronic properties and provides promising possibilities for efficient light-to-energy conversion. Herein, nitrogen-doped ceria (N-CeO2 ) nanoparticles are prepared and then coupled with nitrogen-doped graphene (N-Gr) to create an active and long-lasting N-CeO2 /N-Gr heterocatalyst. Optoelectronic features of N-doping materials ( e.g., plasmon) are significantly improved toward the visible-light region, particularly for 3.9% N-CeO2 /N-Gr nanocomposites. Namely, the 3.9% N-CeO2 possesses numerous catalytic active defects (N states, oxygen vacancy, and Ce 3+ species), leading to a narrow bandgap energy and to the improved plasmonic properties of the ceria host, while the N-Gr preferably serves as an electron scavenger to collect plasmon-generated hot electrons migrating from 3.9% N-CeO2 to drive photocatalytic reactions under the irradiation of visible-light. Resultantly, the 3.9% N-CeO2 /N-Gr photocatalyst delivers an impressive hydrogen evolution reaction (HER) rate of 3.7 μmol mgcat −1 h −1 under visible-light, which is 2.0- and 8.2-fold greater than those obtained from 3.9% N-CeO2 and CeO2 ones, respectively. Additionally, the combination of 3.9% N-CeO2 and N-Gr synergistically produces a long-lasting plasmonic HER photocatalyst system. Metal-free plasmonic N-doped oxides supported by N-doped graphene pave a promising pathway for efficient light-to-hydrogen fuel production accordingly.